IMPLEMENTASI GOOD GOVERNANCE DALAM PELAYANAN PUBLIK DI DESA CINTA DAMAI KECAMATAN TAPUNG HILIR KABUPATEN KAMPAR TAHUN 2021 - Ade Khairun Nisa; Sofyan Hadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Implementation of good governance in providing public services is the application of good governance in implementing public services whose aim is to improve the welfare of society by implementing the principles of transparency, participation and accountability. The problem in this research is that services in Cinta Damai Village are not optimal and there is a gap between the fees requested by the village and the costs incurred by the Kampar Population and Civil Registration Office in processing correspondence. This research is descriptive qualitative research with the main data sources being primary data and secondary data. Data collection techniques were carried out by interviews and review of the literature. Then the data obtained is analyzed in accordance with the principles of good governance from the theory used. The implementation of good governance carried out by the Cinta Damai Village Government in public services is by implementing the first principle, namely transparency through providing information boards with clear requirements, exposing service SOPs on social media, displaying the village government's LKPJ in the form of banners, but in matters of retribution for processing letters. The population administration of the Cinta Damai Village Government did not provide exact details of the fees required for each letter of correspondence. Furthermore, community participation through planned activities, such as the cementization of RT 6-7 in Sumber Mulyo Hamlet and mutual cooperation. The cementing of the road is carried out by the community in a mutual cooperation manner through self-sufficiency management, namely management carried out by the community, and paid to the community, so that it still helps the community's economy, but the level of community participation is still low, one of which is in participating in musrenbang activities, this is due to the village government does not provide a suggestion box for people to freely express their income. The final principle of accountability, the village government serves the community politely in accordance with the second vision of the village in addition to adequate service facilities. Keywords: Transparency, Community Participation, and Accountability.